2011
DOI: 10.1017/s0950268811002147
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic analyses of 111 clinical and environmental O1, O139, and non-O1/O139Vibrio choleraestrains from different geographical areas

Abstract: A total of 111 clinical and environmental O1, O139 and non-O1/O139 Vibrio cholerae strains isolated between 1978 and 2008 from different geographical areas were typed using a combination of methods: antibiotic susceptibility, biochemical test, serogroup, serotype, biotype, sequences containing variable numbers of tandem repeats (VNTRs) and virulence genes ctxA and tcpA amplification. As a result of the performed typing work, the strains were organized into four clusters: cluster A1 included clinical O1 Ogawa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Both (D13 and D15) the strains showed a multiple antibiotic resistance phenotype with resistance to streptomycin, co-trimoxazole, nalidixic acid, ciprofloxacin, ceftaxime and ofloxacin compared to some recent studies where non-O1/non-O139 were susceptible to antibiotics [23,54]. However, enhanced level of resistance to ampicillin, chloramphenicol, fluoroquinolones, cotrimoxazole have been reported by many studies [55][56][57] like the current study. However, the resistance pattern of these non-O1/non-O139 isolates was different from O1 isolates of clinical origin in Pakistan [58].…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…Both (D13 and D15) the strains showed a multiple antibiotic resistance phenotype with resistance to streptomycin, co-trimoxazole, nalidixic acid, ciprofloxacin, ceftaxime and ofloxacin compared to some recent studies where non-O1/non-O139 were susceptible to antibiotics [23,54]. However, enhanced level of resistance to ampicillin, chloramphenicol, fluoroquinolones, cotrimoxazole have been reported by many studies [55][56][57] like the current study. However, the resistance pattern of these non-O1/non-O139 isolates was different from O1 isolates of clinical origin in Pakistan [58].…”
Section: Accepted Manuscriptsupporting
confidence: 58%
“…Given that the environment is dominated by non-O1/non-O139 strains, this observation suggests that these virulence factors probably do not promote fitness in the aquatic niche although there is some data that challenges this conclusion for at least chitin binding lectins (Kirn et al 2005). Various typing methods and deep sequencing has enabled more sensitive surveillance of CTX–ϕ in strains isolated from the environment (Rivera et al 2001; Singh et al 2001; Pang et al 2007; Awasthi et al 2012; Hasan et al 2012; Sealfon et al 2012; Sellek et al 2012). The prevalent assumption that the presence of toxigenic strains in water provides proof that toxigenic strain occupy a stable environmental niche needs to be readdressed with modern methods that might differentiate between contamination of the environment by nearby cholera victims as opposed to these strains maintaining themselves within the environment in the absence of infected humans.…”
Section: Conventional Genomics and Established Virulence Islandsmentioning
confidence: 99%
“…Furthermore, the non-toxigenic O1 isolates in this study were also genetically distinct from the epidemic V. cholerae O1/O139 cluster (GT1), indicating that other unknown virulence factors could be present in the epidemic V. cholerae O1/O139 cluster that are absent in non-toxigenic V. cholerae O1 isolates. Previous studies have shown the presence of non-toxigenic V. cholerae O1 strains in the environment and in humans [6,18,21,27]. Serotyping is therefore not a reliable method for the identification of toxigenic and epidemic V. cholerae O1/O139 strains.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 48 clinical and environmental isolates of V. cholerae and Vibrio mimicus (Table 1) were obtained from Instituto Tecnológico La Marañosa, Spanish Ministry of Defence, San Martín de la Vega, Madrid, Spain, Norwegian Defence Research Establishment, Kjeller, Norway, and Military Institute of Hygiene and Epidemiology, Pulawy, Poland (Table 1) [18-20]. The human isolates were all collected as part of standard patient care.…”
Section: Methodsmentioning
confidence: 99%